Analysis of the competitiveness of coffee exports in Peru - Bustos Chavez, Meliza del Pilar (2022)
Coffee is the most consumed product in the world, including European countries. In this sense, the main objective of this article was to analyse the competitive evolution of Peruvian coffee exports. The data were collected from 2011 to 2020 and were obtained from Sunat-Customs Operations and Trade Map (Trade Intelligence Pages). The analysis was carried out by generating graphs and tables, using minitab 17 Spanish version software. The main destination of parchment coffee was Germany with 46749 tonnes, USA with 53113 tonnes and Belgium with 18445 tonnes. For decaffeinated unroasted coffee beans, the main importer was Germany with 162.47 tonnes. The main importer of decaffeinated roasted coffee was Chile (543.57 tonnes). However, it is noted that exportable parchment coffee from 2011 to 2020 is decreasing by 83,133 tonnes.